The director's role in commercial films and his ability to creatively influence the final output - Sobolev, Igor (2020)
The principal theme of this Bachelor Thesis is getting into details of the director’s job in the commercial production process and reveal hidden parts that might not be obvious for people entering this field. It will cover not only the creative side of this profession, but also what goes behind the scene, which might prove to be much more important, than the ability to work on set.In the theoretic part I will briefly describe basic terminology and cover some of the historical changes that happened in the commercial and filmmaking industry over time. Finally, based on detailed research, the practical part will answer to remaining questions, giving a full picture of a commercial director’s profession, and give advices for beginner directors who are planning to work or have an interest in commercial shooting.